(Not to be Issued) Moltke's Correspondence During the Campaign of 1866 Against Austria : Précis - Wilkinson, Spenser (London Harrisom and Sons, 1915)
Helmuth von Moltke, the ruthless Chief of the Prussian General Staff, achieved a lightning victory over Austria and its German allies in the six-week war of 1866, resulting in hegemony over the disparate German states passing from Vienna to Berlin. This summary of Moltke's military correspondence in the short, sharp war reveals him as a meticulous planner - culminating in the great Prussian victory of Koniggraz in Bohemia (also called Sadowa). Superior Prussian elan and organisation decided the result, despite an Austrian superiority in numbers. Austria lost seven times the number of Prussians killed. This book gives an invaluable insight into a great military mind.
Keywords: Moltke, Helmuth, Graf von, 1800-1891 -- Austro-Prussian War (1866)